2011
DOI: 10.1021/jo2015104
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the Preparation of Allenes Employing Indium- and Zinc-Mediated Dehalogenation Reactions in Aqueous Solutions

Abstract: Simple and mild methods for the synthesis of allenes, employing indium- and zinc-mediated dehalogenation reactions of vicinal dihalides in an aqueous solvent, are described. By using these procedures, various allenylmethyl aryl ethers and monosubstituted allenes have been prepared in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Alkylzinc reagents could be prepared by oxidative insertion of the zinc metal into alkyl halides. However, the method has been limited to the activated halides such as allyl halides and alkyl iodides . Because of the low reactivity of the alkyl bromides or chlorides, the preparation of organozinc compounds derived from these compounds usually require highly reactive Rieke-zinc or activators such as 1,2-dibromoethane/Me 3 SiCl/alkali iodide, I 2 or LiCl in dry solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylzinc reagents could be prepared by oxidative insertion of the zinc metal into alkyl halides. However, the method has been limited to the activated halides such as allyl halides and alkyl iodides . Because of the low reactivity of the alkyl bromides or chlorides, the preparation of organozinc compounds derived from these compounds usually require highly reactive Rieke-zinc or activators such as 1,2-dibromoethane/Me 3 SiCl/alkali iodide, I 2 or LiCl in dry solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Different methodologies have been explored for the specific production of organozinc compounds: , transmetalation of organo-lithiated derivatives in the presence of ZnX 2 , boron/Zn exchange from boronates, palladozincation of propargyl benzoates or mesylates, direct zincation of propargyl halides, Zn-mediated Barbier reactions and Brook rearrangement . Comparatively, procedures involving iodine/Zn exchange from the corresponding propargyl iodides or allenyl iodides have scarcely been exploited . Closely related In-mediated reactions have also been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al have reported that terminal allenes 148 can be obtained in high yields by reduction of vicinal dihalides 147 with zinc or indium (Scheme 35c). [85] Scheme 35. Formation of allenes by reduction with zinc…”
Section: Elimination Of Zincmentioning
confidence: 99%